A comparative study of ondansetron and granisetron in combination with dexamethasone-in prophylaxis for postoperative nausea and vomiting (PONV) in laproscopic cholecystectomies - Nanjundaswamy, Nethra H.; Sridhara, Raghavendra Biligiri (International Journal of Research in Medical Sciences, 2018)
Background: Post operative nausea and vomiting (PONV) is a common problem and distressing symptom in surgical patient population. General anaesthesia with inhalational agents is associated with an average PONV incidence of 20-30 % in surgical patients. PONV is difficult to treat and needs multiple drugs and combination of drugs. Granisetron and Ondansetron are among the commonly used 5HT3 antagonists and used in combination with dexamethasone for prophylaxis against PONV. The aim of the study was to compare the efficacy of combination of antiemetics-Ondansetron 4mg+Dexamethasone 8mg and Granisetron 1mg+Dexamethasone 8mg in prevention of post operative nausea and vomiting. Methods: 75 patients of ASA 1 and 2 were randomly allocated to three groups-Group 1 (n=25) received Ondansetron 4mg+Dexamethasone 8mg; Group 2 (n=25)-received Granisetron 1mg+Dexamethasone 8mg; Group 3-received saline with dexamethasone 8mg. Standard general anaesthesia protocol was followed. Study drugs were administered at the time of induction. Post operative nausea and vomiting was studied for period of 24hrs. Severity was assessed using PONV Score (0=no nausea;1=nausea only;2=retching;3=vomiting). The adverse effects were also studied. Results: The incidence of PONV was 16% in Group 1 and 2 and 68% in Group 3. The complete response after 24hr period was 32% in control group, 84% in Group 1 and Group 2. Rescue antiemetics were required only in control group. There was no statistical difference noted between Group 1 and Group 2 but there was clinical and statistical significance noted between groups which received prophylactic antiemetic combination and control. Adverse effects were not observed in any group. Conclusions: Granisetron 1mg and Ondansetron 4mg in combination with dexamethasone 8mg are equally effective and safe in decreasing the incidence of post operative nausea and vomiting in laproscopic cholecystectomies under general anaesthesia.